2019
DOI: 10.1016/j.trc.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing drivers’ preferences and choices for the content and format of variable message signs (VMS)

Abstract: Background: Recent advance in variable message signs (VMS) technology has made it viable to provide spatio-temporal information on traffic and network conditions to drivers. There is a debate whether VMS diverts drivers' attention away from the road and may cause unnecessary distraction in their driving tasks due to inconsistent VMS contents and formats. There are also other external factors such as weather conditions, visibility and time of day that may affect the integrity and reliability of the VMS. In Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…This may be related to the fact that inexperienced office car drivers have higher demand for traffic information than well experienced ones [ 45 ], hence they are satisfied with the formats and contents of VMS. In addition, the drivers’ decision-making of office car drivers is affected by gender and driving experience (coefficient = 0.605, p < 0.01; coefficient = 0.314, p < 0.01), a finding which confirms the conclusion reached by Zhao et al [ 23 ], who concluded that less experienced and young drivers are more likely to divert to an alternative route. Driving experience has a negative impact on the perceived effectiveness and quality of VMS (coefficient = -0.171, p < 0.05; coefficient = -0.355, p < 0.01), implying that office car drivers with less driving experience often think that the information provided by VMS is accurate, reliable and necessary for travelers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This may be related to the fact that inexperienced office car drivers have higher demand for traffic information than well experienced ones [ 45 ], hence they are satisfied with the formats and contents of VMS. In addition, the drivers’ decision-making of office car drivers is affected by gender and driving experience (coefficient = 0.605, p < 0.01; coefficient = 0.314, p < 0.01), a finding which confirms the conclusion reached by Zhao et al [ 23 ], who concluded that less experienced and young drivers are more likely to divert to an alternative route. Driving experience has a negative impact on the perceived effectiveness and quality of VMS (coefficient = -0.171, p < 0.05; coefficient = -0.355, p < 0.01), implying that office car drivers with less driving experience often think that the information provided by VMS is accurate, reliable and necessary for travelers.…”
Section: Discussionsupporting
confidence: 82%
“…To make up for this deficiency, the structural equation modelling (SEM) has been used to evaluate perceived service quality in the aspect of public transport [ 22 , 23 ], rail transit [ 24 ], water transit [ 25 ], as well as traffic information system [ 26 ]. However, SEM is difficult to deal with individual characteristics because they affect perceived quality as casual variables rather than indicator variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…text vs. pictograms, or even maps demonstrating the relevant information, e.g. travel time on different routes and so on, has also been found to affect driver behaviour [33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the effectiveness of information presented on VMS using surveys ( 9 – 11 ), driving simulators ( 9 , 12 18 ), or field experiments ( 15 , 19 ). Some of these works studied how VMS could affect route choice (e.g., 10 , 11 , 15 ) and found that VMS could lead to up to 10% of travelers changing routes based on information displayed on VMS.…”
mentioning
confidence: 99%
“…While VMS have been used extensively within the U.S.A. for many years, recent improvements in signing technology now allow for their greater use and for a variety of colored fonts, backgrounds, and ancillary information (e.g., route markers/shields) on these signs. While it is anticipated that the use of color on these signs could yield performance gains, only a few research studies have explored the most effective way to utilize this new technology to improve the comprehensibility and visibility of VMS for conveying travel time information ( 9 , 16 18 , 20 ). Most of these studies have relied on results of laboratory tests, and found that too much text and too many colors could reduce participants’ comprehension of signs ( 16 ); participants responded quickest to two-line messages (as opposed to one or three lines) and to two-color signs (as opposed to one or three colors) specifically for Chine VMS ( 17 ); on graphical representations of the road network, using road color only to present traffic conditions had the fastest response time, as compared with displaying traffic speed or presenting journey times, again for Chines VMS ( 18 ); and that drivers of large trucks preferred signs on which congestion was color coded ( 20 ).…”
mentioning
confidence: 99%